Hip and distal femur fracture outcomes over three successive UK lockdown periods during the COVID- 19 pandemic: what have we learnt?. (2021) - Sadiq, S.; Lipski, C.; Hanif, U- K.; Arshad, F.; Chaudary, M.; Chaudhry, F.
No abstract available